Inhibition of NLRP1 inflammasome improves autophagy dysfunction and Aβ disposition in APP/PS1 mice - Li, Xuewang; Zhang, Han; Yang, Liu; Dong, Xianan; Han, Yuli; Su, Yong; Li, Weiping; Li, Weizu (Behavioral and brain functions, 2023)
Increasing evidence has shown that the NOD-like receptor protein 1 (NLRP1) inflammasome is associated with Aβ generation and deposition, which contributes to neuronal damage and neuronal-inflammation in Alzheimer's disease (AD). However, the specific mechanism of NLRP1 inflammasome in the pathogenesis of AD is still unclear. It has been reported that autophagy dysfunction can aggravate the pathological symptoms of AD and plays an important role in regulating Aβ generation and clearance. We hypothesized that NLRP1 inflammasome activation may induce autophagy dysfunction contributing to the progression of AD. In the present study, we observed the relationship between Aβ generation and NLRP1 inflammasome activation, as well as AMPK/mTOR mediated-autophagy dysfunction in WT 9-month-old (M) mice, APP/PS1 6 M and APP/PS1 9 M mice. Additionally, we further studied the effect of NLRP1 knockdown on cognitive function, Aβ generation, neuroinflammation and AMPK/mTOR mediated autophagy in APP/PS1 9 M mice. Our results indicated that NLRP1 inflammasome activation and AMPK/mTOR mediated-autophagy dysfunction are closely implicated in Aβ generation and deposition in APP/PS1 9 M mice, but not in APP/PS1 6 M mice. Meanwhile, we found that knockdown of NLRP1 significantly improved learning and memory impairments, decreased the expressions of NLRP1, ASC, caspase-1, p-NF-κB, IL-1β, APP, CTF-β, BACE1 and Aβ 1-42 , and decreased the level of p-AMPK, Beclin 1 and LC3 II, and increased the level of p-mTOR and P62 in APP/PS1 9 M mice. Our study suggested that inhibition of NLRP1 inflammasome activation improves AMPK/mTOR mediated-autophagy dysfunction, resulting in the decrease of Aβ generation, and NLRP1 and autophagy might be important targets to delay the progression of AD.